Nicosulfuron-atrazine mesotrione oil suspending agent and preparation method thereof
Through the preparation method of nycopyridium atrazine oil suspension agent, the problems of poor suspension effect, easy precipitation and poor water resistance of existing suspension agents are solved by using atrazine, nycopyrisulfuron, nitrosulfurone compounding, starch-coated fat-soluble resin, nanodispersed fibers and other components, and the effects of high suspension rate, stability and water resistance are achieved.
Patent Information
- Application Number
- CN202411639665.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-18
AI Technical Summary
The existing suspension agents prepared by compounding the three nicopyridium sulfonate atrazine have poor suspension effect, prone to precipitation, and poor water resistance when used, which affects the herbicidal effect.
The preparation method of niacin niacin oil suspension agent is adopted, and the combination of atrazine, niacin sulfonone, and combined with starch coated with fat-soluble resin, nanodispersed fibers, emulsifiers and other components is formed to form a suspension agent with high suspension rate and stability.
The advantages of the suspension agent are achieved, such as high suspension rate, high stability, good water resistance and long weed control time, ensuring the durability and stability of the weeding effect.
Abstract
Description
Technical Field
[0001] The present application relates to the field of herbicides, and more specifically, to a nicotine sulfonate and atrazine oil suspension and a preparation method thereof. Background Art
[0002] Atrazine, also known as atrazine, has a chemical name of 2-chloro-4-ethylamino-6-isopropylamino-1,3,5-triazine. It is an organic compound with a chemical formula of C8H14ClN5 and is a triazine herbicide.
[0003] Nicosulfuron is a systemic sulfonylurea herbicide that can be absorbed by the stems, leaves and roots of plants and quickly transmitted, inhibiting the activity of acetolactate synthase, organizing cell division, and thus stopping the growth of some sensitive plants; Mesotrione is an organic compound, a benzoylcyclohexanedione herbicide, an effective competitive hydroxyphenylpyruvate dioxygenase (HPPD) enzyme inhibitor, selective for corn crops, fast metabolism in susceptible crops, and high tolerance.
[0004] The existing suspensions prepared by mixing nicotine, nitrate, sulfonate and atrazine are mostly wet powders or water suspensions. The wet powders need to be diluted twice when used, and are prone to moisture absorption and agglomeration in a dry environment, affecting stability. The water suspension has a poor suspension effect and is prone to precipitation. In addition, during rainfall, the water suspension is easily washed away from the surface of weeds by rainwater, affecting the weed control effect.
[0005] Therefore, how to prepare a new nicotine sulfonate atrazine oil suspension concentrate, which has the advantages of high suspension rate, high stability, good water resistance and long weed control time, is a problem to be solved. Summary of the invention
[0006] In order to prepare a new nicotinate sulfonate atrazine oil suspension, which has the advantages of high suspension rate, high stability, good water resistance and long weed control time, the present application provides a nicotinate sulfonate atrazine oil suspension and a preparation method thereof.
[0007] In the first aspect, the present application provides a nicotine nitrate sulfonate atrazine oil suspension, which adopts the following technical solution: A nicosulfuron-atrazine oil suspension comprises the following raw materials in parts by weight: 40-50 parts of atrazine, 5-12 parts of nicosulfuron, 10-16 parts of mesotrione, 15-22 parts of an emulsifier, 1-3 parts of a starch-coated fat-soluble resin, 1-3 parts of nano-dispersed fibers, 1-2 parts of a dispersant, 1-3 parts of a thickener, 0.5-1 parts of a defoaming agent, and 50-60 parts of an oil solvent.
[0008] By adopting the above technical scheme, atrazine, nicosulfuron and mesotrione are compounded to make the suspension concentrate have the advantages of quickly killing weeds in a short time, and the weed killing range is wide and the weed control time is long; in combination with oil solvent and emulsifier, the finished product has the advantages of high suspension rate, and the oil solvent can improve the water resistance of the finished product, and the suspension concentrate is not easily separated from the weed surface due to rain erosion; at the same time, the thickener can improve the adhesion stability of the suspension concentrate on the weed surface, and further prevent the suspension concentrate from being easily separated from the weed surface by rain erosion.
[0009] The starch-coated fat-soluble resin and the nano-dispersed fiber are matched. The starch has a certain oil absorption. The oil solvent can gradually pass through the starch and contact the fat-soluble resin, and the fat-soluble resin gradually dissolves. This can not only improve the bonding effect and dispersion stability of the starch-coated fat-soluble resin and the oil solvent, but also the fat-soluble resin has good water resistance, which can prevent rainwater from washing away the suspending agent on the surface of weeds, thereby ensuring the adhesion stability of the suspending agent on the surface of weeds; the nano-dispersed fiber utilizes the larger specific surface area of the fiber and cooperates with the thickener to promote the dispersion of the nano-dispersed fiber in the suspending agent, and the fiber and starch are convenient for carrying atrazine, nicosulfuron and mesotrione to adhere to the surface of weeds, thereby achieving the advantages of efficient and rapid weed removal and weed control.
[0010] Preferably, the starch-coated fat-soluble resin is made of a starch composite liquid and coumarone resin in a mass ratio of 1:1-3.
[0011] By adopting the above technical scheme, the starch composite liquid and the coumarone resin are matched, and the good bonding effect of the starch composite liquid is utilized to adhere to the particle surface of the coumarone resin. After the starch composite liquid is dried to form a film, the film layer is porous. The porous film layer cooperates with the adsorption effect of starch on the oil solvent, which is convenient for the adsorption of the oil solvent to contact the coumarone resin. The coumarone resin gradually dissolves and produces viscosity, further improving the bonding effect between the starch-coated fat-soluble resin and the oil solvent. In addition, the adsorption effect of starch is convenient for the adsorption of atrazine, nicosulfuron, and mesotrione, which are evenly dispersed in the suspending agent and can be evenly sprayed on the surface of weeds, so that the suspending agent can be stably attached to the surface of the weeds, thereby quickly removing the weeds. At the same time, the starch is light in weight, which further ensures the high suspension rate of the suspending agent.
[0012] When washed by rain, coumarone resin has a higher viscosity, which can ensure that the suspension agent is not easily washed away by rain and separated from the surface of weeds, affecting the effect of the suspension agent; and coumarone and quality have good water resistance, which can further block moisture, ensure that the suspension agent is stably attached to the surface of weeds, and improve the adhesion stability of the suspension agent on the surface of weeds.
[0013] Preferably, the starch composite solution is made of starch solution, phospholipid, glutaraldehyde and sodium alginate solution in a mass ratio of 1:0.2-0.3:0.1-0.2:0.4-0.8.
[0014] By adopting the above technical scheme, the bonding effect of starch solution and sodium alginate solution is combined with the filling effect of phospholipids and the cross-linking effect of glutaraldehyde, so that the starch composite liquid is easy to form a porous and breathable film layer after drying. At the same time, the lipophilic effect of phospholipids cooperates with the adsorption effect of starch on oil solvents to promote the contact between the oil solvents and the coumarone resin, thereby ensuring the dissolution effect of the coumarone resin and improving the suspension rate of the suspension agent and the adhesion stability on the surface of weeds; at the same time, under the action of the emulsifier, the starch solution, sodium alginate solution and oil solvent are promoted to be mixed evenly, thereby ensuring the dispersion stability of the raw materials in the suspension agent.
[0015] Preferably, the nano-dispersed fibers are made of cellulose nano-fibers, chitosan fibers and hydrogenated rosin resin in a mass ratio of 1:0.1-0.5:0.2-0.6.
[0016] By adopting the above technical scheme, the contact area between the fiber and atrazine, nicosulfuron and mesotrione can be increased by utilizing the large specific surface area of cellulose nanofibers and chitosan fibers in combination with the hydrogenated rosin resin on the fiber surface. The fat-soluble effect of the hydrogenated rosin resin is utilized to facilitate the attraction of oil solvents and gradually dissolve to generate viscosity, which not only improves the dispersion uniformity of the cellulose nanofibers and chitosan fibers in the oil solvent, but also improves the stability of the fibers in the suspending agent, making it less likely to have precipitation problems. The lightweight effect of the fibers facilitates the adsorption of atrazine, nicosulfuron and mesotrione, thereby improving the suspension rate of the suspending agent. At the same time, the oil-soluble effect of the hydrogenated rosin resin is utilized to provide good waterproof and water resistance on the surface of weeds, thereby improving the resistance to rain scouring and ensuring the adhesion stability of the suspending agent on the surface of weeds.
[0017] Preferably, the cellulose nanofibers are made of cellulose nanofiber filaments and sodium carboxymethyl cellulose solution in a mass ratio of 1:0.1-0.3.
[0018] By adopting the above technical scheme, cellulose nanofibers and sodium carboxymethyl cellulose solution are matched, and the sodium carboxymethyl cellulose solution can be uniformly mixed with the oil solvent under the action of an emulsifier; the leaves on the surface of weeds are often hydrophobic and lipophilic due to the presence of a wax layer. When the suspension agent is used for a long time, atrazine, nicosulfuron and mesotrione gradually penetrate into the weeds under the action of the oil solvent, destroy the cell walls of the weeds and gradually kill the weeds. The internal cells of the weeds have a certain hydrophilicity. The sodium carboxymethyl cellulose has viscosity under the action of water, which makes it easy for the cellulose nanofibers to adhere to the surface of the weeds, further ensuring the adhesion stability of the suspension agent on the surface of the weeds; at the same time, when the water resistance of the suspension agent deteriorates due to long-term rain erosion, the viscous solution formed by the sodium carboxymethyl cellulose in contact with water can also improve the adhesion stability of the suspension agent on the surface of the weeds.
[0019] Preferably, the chitosan fiber is made of chitosan fiber filaments and chitosan quaternary ammonium salt solution in a mass ratio of 1:0.2-0.4.
[0020] By adopting the above technical scheme, chitosan fiber filaments and chitosan quaternary ammonium salt solution have certain antibacterial and bactericidal effects, and are combined with atrazine, nicosulfuron and mesotrione to further achieve the removal and killing of weeds. The large specific surface area of chitosan fiber filaments facilitates the adsorption of atrazine, nicosulfuron and mesotrione. The chitosan fiber filaments are stably bonded to the surface of weeds, so that atrazine, nicosulfuron and mesotrione act evenly on the surface of weeds, and the suspension agent is not easily separated from the weed surface due to rain erosion, thereby ensuring the stability of the suspension agent while ensuring the removal and control of weeds.
[0021] Preferably, the dispersant is composed of sodium lignin sulfonate and citric acid fatty acid glyceride in a mass ratio of 1:0.1-0.5.
[0022] By adopting the above technical scheme, sodium lignin sulfonate and citric acid fatty acid glyceride are matched, sodium lignin sulfonate is convenient for dispersing starch-coated fat-soluble resin, and citric acid fatty acid glyceride has both hydrophilic and lipophilic groups, which is convenient for connecting nano-dispersed fibers and oil solvents, ensuring that the starch-coated fat-soluble resin and the nano-dispersed fibers are evenly dispersed in the suspending agent, ensuring the suspension rate while preventing precipitation and aggregation, and ensuring the stability of the suspending agent.
[0023] Preferably, the emulsifier is castor oil polyoxyethylene ether.
[0024] By adopting the above technical solution, castor oil polyoxyethylene ether has good emulsification and can improve the stability of the suspension.
[0025] Preferably, the oil solvent consists of soybean oil, palm oil and orange oil in a mass ratio of 1:0.2-0.4:0.1-0.3.
[0026] By adopting the above technical scheme, hydrogenated rosin resin is dissolved in orange oil, and coumarone resin is dissolved in soybean oil and palm oil in vegetable oil, which can not only ensure the suspension rate of the suspending agent, but also ensure the adhesion stability of the suspending agent on the surface of weeds. At the same time, the suspending agent can also withstand rain erosion and is not easy to fall off the surface of weed leaves, thereby ensuring the adhesion stability of the suspending agent on the surface of weed leaves.
[0027] In the second aspect, the present application provides a method for preparing a nicotine nitrate sulfonate atrazine oil suspension, using the following technical solution: A method for preparing a nicotine nitrate sulfonate atrazine oil suspension comprises the following steps: S1, mixing and emulsifying the oil solvent and the emulsifier uniformly to obtain an emulsified solvent; S2, adding atrazine, nicosulfuron and mesotrione to the emulsified solvent, mixing and stirring evenly, and then sand-milling to obtain a mixture; S3. Add starch-coated fat-soluble resin, nano-dispersed fiber, dispersant, thickener and defoamer into the mixture, mix and stir evenly, and defoam to obtain the finished product.
[0028] By adopting the above technical scheme, the prepared suspension concentrate has the advantages of high suspension rate, high stability, good water resistance and long weed control time.
[0029] In summary, this application has the following beneficial effects: 1. By compounding atrazine, nicosulfuron and mesotrione, the suspension concentrate has the advantages of quickly killing weeds in a short time, with a wide weed killing range and a long weed control time; by combining with oil solvent and emulsifier, the finished product has the advantages of high suspension rate, and the oil solvent can improve the water resistance of the finished product, and it is not easy for the suspension concentrate to be separated from the weed surface due to rain erosion; at the same time, the thickener can improve the adhesion stability of the suspension concentrate on the weed surface, further preventing the suspension concentrate from being easily separated from the weed surface by rain erosion.
[0030] 2. Nicosulfuron, mesotrione, starch-coated fat-soluble resin, and nano-dispersed fibers are combined. The sulfonyl and amino groups in Nicosulfuron are combined with the sulfonyl groups in mesotrione to attract and bond with starch and fibers. The lightweight effect and large specific surface area of starch and fiber can load Nicosulfuron and mesotrione. When sprayed on the surface of weeds, the high suspension rate and adhesion stability make the suspension agent stably adhere to the surface of weeds, achieving the effect of killing weeds and long-term weed control. At the same time, the presence of fat-soluble resin and hydrogenated rosin resin can improve the water resistance effect, avoid rain erosion to separate the suspension agent from the weed surface, and further ensure the adhesion stability of the suspension agent on the weed surface under rain erosion conditions. DETAILED DESCRIPTION
[0031] The present application is further described in detail below with reference to the embodiments.
[0032] Preparation example of starch-coated fat-soluble resin The following raw materials are all commercially available.
[0033] Preparation Example 1: Starch-coated fat-soluble resin is prepared by the following method: Weigh 1 kg of starch solution, 0.2 kg of phospholipid, 0.1 kg of glutaraldehyde and 0.6 kg of sodium alginate solution, mix them, and stir them at a speed of 1000 r / min and 45° C. for 20 min to obtain a starch composite solution; the starch solution is a 2% starch aqueous solution by mass, the phospholipid is soybean lecithin, and the sodium alginate solution is a 1% sodium alginate aqueous solution by mass; 1 kg of starch composite liquid was evenly sprayed on the surface of 2 kg of coumarone resin, the average particle size of the coumarone resin was 5 μm, and the coumarone resin was dried and dispersed until the coumarone resins did not stick to each other and agglomerated, thereby obtaining a finished product of starch-coated fat-soluble resin.
[0034] Preparation Example 2: This preparation example differs from Preparation Example 1 in that: Weigh 1 kg of starch solution, 0.2 kg of phospholipid, 0.1 kg of glutaraldehyde, and 0.4 kg of sodium alginate solution, mix them, and stir them at a speed of 1000 r / min and 45° C. for 20 min to obtain a starch composite solution; 1 kg of starch composite liquid is evenly sprayed on the surface of 1 kg of coumarone resin, and the mixture is dried and dispersed until the coumarone resins are not adhered to each other and agglomerated, so as to obtain a finished product of starch-coated fat-soluble resin.
[0035] Preparation Example 3: This preparation example differs from Preparation Example 1 in that: Weigh 1 kg of starch solution, 0.3 kg of phospholipid, 0.2 kg of glutaraldehyde, and 0.8 kg of sodium alginate solution, mix them, and stir them at a speed of 1000 r / min and 45° C. for 20 min to obtain a starch composite solution; 1 kg of starch composite liquid was evenly sprayed on the surface of 3 kg of coumarone resin, and the mixture was dried and dispersed until the coumarone resins did not stick to each other and agglomerated, thereby obtaining a finished product of starch-coated fat-soluble resin.
[0036] Preparation example of nano-dispersed fibers Among the following raw materials, chitosan quaternary ammonium salt was purchased from Jiangsu Jiujia Biotechnology Co., Ltd.; cellulose nanofiber filaments were purchased from Hubei Shineng Chemical Technology Co., Ltd.; other raw materials were all commercially available.
[0037] Preparation Example 4: Nano-dispersed fibers are prepared by the following method: 0.2 kg of sodium carboxymethyl cellulose solution is evenly sprayed on the surface of 1 kg of cellulose nanofibers, and the cellulose nanofibers are dried and dispersed until the cellulose nanofibers are not adhered to each other and agglomerated, so as to obtain cellulose nanofibers; the average length of the cellulose nanofibers is 3 μm, and the average diameter is 20 nm; the sodium carboxymethyl cellulose solution is a 1% by mass sodium carboxymethyl cellulose aqueous solution; 0.3 kg of chitosan quaternary ammonium salt solution is uniformly sprayed on the surface of 1 kg of chitosan fiber filaments, and the chitosan fiber filaments are dried and dispersed until the chitosan fiber filaments are not adhered to each other and agglomerated, so as to obtain chitosan fiber; the average length of the chitosan fiber is 5 μm, and the average diameter is 20 nm; the chitosan quaternary ammonium salt solution is a chitosan quaternary ammonium salt aqueous solution with a mass fraction of 1%; The hydrogenated rosin is heated to 100°C to soften, thereby obtaining hydrogenated rosin liquid; After 1 kg of cellulose nanofibers and 0.3 kg of chitosan fibers are uniformly mixed, 0.4 kg of hydrogenated rosin solution is evenly sprayed on the surface, and the mixture is dried and dispersed until the cellulose nanofibers and chitosan fibers are not adhered to each other and agglomerated, to obtain a finished product.
[0038] Preparation Example 5: This preparation example differs from Preparation Example 4 in that: 0.1 kg of sodium carboxymethyl cellulose solution was evenly sprayed on the surface of 1 kg of cellulose nanofibers, and the cellulose nanofibers were dried and dispersed until the cellulose nanofibers did not stick to each other and agglomerated, thereby obtaining cellulose nanofibers; 0.2 g of chitosan quaternary ammonium salt solution was uniformly sprayed on the surface of 1 kg of chitosan fiber filaments, and the chitosan fiber filaments were dried and dispersed until they were not adhered to each other and agglomerated, thereby obtaining chitosan fiber; After 1 kg of cellulose nanofibers and 0.1 kg of chitosan fibers are uniformly mixed, 0.2 kg of hydrogenated rosin solution is evenly sprayed on the surface, and the mixture is dried and dispersed until the cellulose nanofibers and chitosan fibers are not adhered to each other and agglomerated, to obtain a finished product.
[0039] Preparation Example 5: This preparation example differs from Preparation Example 4 in that: 0.3 kg of sodium carboxymethyl cellulose solution was evenly sprayed on the surface of 1 kg of cellulose nanofibers, and the solution was dried and dispersed until the cellulose nanofibers did not stick to each other and agglomerated, thereby obtaining cellulose nanofibers; 0.4 kg of chitosan quaternary ammonium salt solution was uniformly sprayed on the surface of 1 kg of chitosan fiber filaments, and the chitosan fiber filaments were dried and dispersed until they were not adhered to each other and agglomerated, thereby obtaining chitosan fiber; After 1 kg of cellulose nanofibers and 0.5 kg of chitosan fibers are uniformly mixed, 0.6 kg of hydrogenated rosin solution is evenly sprayed on the surface, and the mixture is dried and dispersed until the cellulose nanofibers and chitosan fibers are not adhered to each other and agglomerated, to obtain a finished product. Example
[0040] The following raw materials are all commercially available.
[0041] Example 1: A nicotine nitrate sulfonate atrazine oil suspension: 45kg of atrazine, 10kg of nicosulfuron, 14kg of mesotrione, 19kg of emulsifier, 2kg of starch-coated fat-soluble resin, 2kg of nano-dispersed fiber, 1.5kg of dispersant, 2kg of thickener, 1kg of defoamer, and 55kg of oil solvent; the emulsifier is castor oil polyoxyethylene ether; the starch-coated fat-soluble resin is the starch-coated fat-soluble resin prepared in Preparation Example 1; the nano-dispersed fiber is the nano-dispersed fiber prepared in Preparation Example 4; the dispersant is composed of sodium lignin sulfonate and citric acid fatty acid glyceride in a mass ratio of 1:0.3; the thickener is white oil; the defoamer is an organosilicon defoamer; the oil solvent is composed of soybean oil, palm oil and orange oil in a mass ratio of 1:0.3:0.2; The preparation method is as follows: S1, mixing and emulsifying the oil solvent and the emulsifier uniformly to obtain an emulsified solvent; S2, adding atrazine, nicosulfuron and mesotrione to the emulsified solvent, stirring at 1000 r / min for 20 min, and after mixing evenly, sand-milling to a particle size D90 of less than 5 μm to obtain a mixture; S3. Add starch-coated fat-soluble resin, nano-dispersed fiber, dispersant, thickener and defoamer into the mixture, stir at 1000 r / min for 10 min, mix evenly, and perform vacuum defoaming treatment to obtain the finished product.
[0042] Embodiment 2: This embodiment differs from Embodiment 1 in that: 40kg of atrazine, 5kg of nicosulfuron, 10kg of mesotrione, 15kg of emulsifier, 1kg of starch-coated fat-soluble resin, 1kg of nano-dispersed fiber, 1kg of dispersant, 1kg of thickener, 0.5kg of defoamer, and 50kg of oil solvent; the emulsifier is castor oil polyoxyethylene ether; the starch-coated fat-soluble resin is the starch-coated fat-soluble resin prepared in Preparation Example 2; the nano-dispersed fiber is the nano-dispersed fiber prepared in Preparation Example 5; the dispersant is composed of sodium lignin sulfonate and citric acid fatty acid glyceride in a mass ratio of 1:0.1; the thickener is white oil; the defoamer is a silicone defoamer; the oil solvent is composed of soybean oil, palm oil and orange oil in a mass ratio of 1:0.2:0.1.
[0043] Embodiment 3: This embodiment differs from Embodiment 1 in that: 50kg of atrazine, 12kg of nicosulfuron, 16kg of mesotrione, 22kg of emulsifier, 3kg of starch-coated fat-soluble resin, 3kg of nano-dispersed fiber, 2kg of dispersant, 3kg of thickener, 1kg of defoamer, and 60kg of oil solvent; the emulsifier is castor oil polyoxyethylene ether; the starch-coated fat-soluble resin is the starch-coated fat-soluble resin prepared in Preparation Example 3; the nano-dispersed fiber is the nano-dispersed fiber prepared in Preparation Example 6; the dispersant is composed of sodium lignin sulfonate and citric acid fatty acid glyceride in a mass ratio of 1:0.5; the thickener is white oil; the defoamer is a silicone defoamer; the oil solvent is composed of soybean oil, palm oil and orange oil in a mass ratio of 1:0.4:0.3.
[0044] Embodiment 4: This embodiment differs from Embodiment 1 in that: No phospholipids were added to the starch composite solution in the starch-coated fat-soluble resin.
[0045] Embodiment 5: This embodiment differs from Embodiment 1 in that: No hydrogenated rosin resin is added to the nano-dispersed fibers.
[0046] Embodiment 6: This embodiment differs from Embodiment 1 in that: In the nanodispersed fibers, the cellulose nanofibers and chitosan fibers were replaced by glass fibers of equal mass.
[0047] Embodiment 7: This embodiment differs from Embodiment 1 in that: In the nano-dispersed fibers, cellulose nanofibers are replaced by cellulose nanofiber filaments of equal mass, and chitosan fibers are replaced by chitosan fiber filaments of equal mass.
[0048] Embodiment 8: This embodiment differs from Embodiment 1 in that: No citric acid fatty acid glyceride was added to the dispersant.
[0049] Comparative Example Comparative Example 1: The difference between this comparative example and Example 1 is that: The starch-coated coumarone resin is replaced by coumarone resin of equal mass in the raw materials.
[0050] Comparative Example 2: The difference between this comparative example and Example 1 is that: The starch coated coumarone resin is replaced by starch of equal mass in the raw materials.
[0051] Performance testing 1. Suspension test The suspensions were prepared by the preparation methods of Examples 1-8 and Comparative Examples 1-2, respectively, and the suspension rates were calculated and the data were recorded.
[0052] 2. Stability test The suspensions were prepared by the preparation methods of Examples 1-8 and Comparative Examples 1-2, respectively. The suspensions were allowed to stand for 3 days, and the precipitation scores were recorded. The scoring criteria were as follows: no precipitation 10 points → all particles were precipitated, showing obvious stratification 0 points.
[0053] 3. Water resistance test The suspension concentrates were prepared by the preparation methods of Examples 1-8 and Comparative Examples 1-2, respectively. 10 g of weed leaves were weighed for each group of Examples or Comparative Examples, and recorded as the initial mass. The suspension concentrate was sprayed on the surface of one side of the weed leaves at an addition amount of 1 mL per gram of weeds. After standing for 12 hours, the leaf surface sprayed with the suspension concentrate was washed with a rainfall of 10 kg / h for 1 hour, the water on the surface of the weeds was drained, and then the mass of the weed leaves was weighed, recorded as the mass after rain washing, and the difference between the mass before and after was recorded = the mass after rain washing - the initial mass; the larger the difference, the less the amount of suspension concentrate washed away by rain, and the smaller the difference, the greater the amount of suspension concentrate washed out from the leaf surface by rain.
[0054] Table 1 Performance test table project Suspension rate / % Score / points Difference / g Example 1 98.2 9.0 6.35 Example 2 97.6 8.0 6.18 Example 3 98.5 9.5 6.40 Example 4 97.1 7.0 5.97 Example 5 92.3 5.5 4.46 Example 6 93.8 6.0 4.89 Example 7 96.4 8.5 5.25 Example 8 95.7 7.5 5.03 Comparative Example 1 94.1 7.0 4.95 Comparative Example 2 90.5 4.0 4.02 It can be seen from Examples 1-3 and Table 1 that the suspension concentrate prepared in the present application has a high suspension rate and a high stability score. At the same time, the suspension concentrate is not easy to separate from the leaf surface after being washed by rainwater, thereby ensuring the weed removal and control effects.
[0055] Combining Example 1 and Examples 4-8 and Table 1, it can be seen that no phospholipids are added to the starch composite liquid in the starch-coated fat-soluble resin in Example 4. Compared with Example 1, the suspension rate of the suspension concentrate in Example 4 is lower than that in Example 1, and the stability score is lower than that in Example 1, and the difference is smaller than that in Example 1; this indicates that the addition of phospholipids can stabilize the raw materials in the suspension concentrate, and that phospholipids can improve the dispersion stability of the starch-coated fat-soluble resin in the oil solvent, and that phospholipids are hydrophobic and water-resistant, and can protect the suspension concentrate on the weed leaves from rain erosion.
[0056] No hydrogenated rosin resin is added to the nano-dispersed fibers of Example 5. Compared with Example 1, the suspension rate of the suspending agent of Example 5 is lower than that of Example 1, and the stability score is lower than that of Example 1, and the difference is smaller than that of Example 1; this indicates that the hydrogenated rosin resin is soluble in the oil solvent, which improves the adhesion stability and dispersion stability of the suspending agent, ensures that the suspending agent is stably attached to the surface of weeds and is resistant to rain erosion, and at the same time improves the suspension rate of the raw materials in the suspending agent. The higher viscosity is not prone to precipitation problems, thereby ensuring the stability of the suspending agent.
[0057] In the nano-dispersed fibers of Example 6, the cellulose nanofibers and chitosan fibers were replaced with glass fibers of equal mass. Compared with Example 1, the suspension rate of the suspending agent of Example 6 was lower than that of Example 1, and the stability score was lower than that of Example 1, and the difference was smaller than that of Example 1; this indicates that the glass fibers cannot load atrazine, nicosulfuron, and mesotrione, which affects the suspension rate and stability of the suspending agent, and are not easy to adhere to oil solvents, and are easily detached from the surface of weed leaves during rain scouring.
[0058] In the nano-dispersed fibers of Example 7, cellulose nanofibers are replaced with cellulose nanofiber filaments of equal mass, and chitosan fibers are replaced with chitosan fibers of equal mass. Compared with Example 1, the suspension rate of the suspending agent of Example 7 is lower than that of Example 1, and the stability score is lower than that of Example 1, and the difference is smaller than that of Example 1; this indicates that the sodium carboxymethyl cellulose solution on the surface of the cellulose nanofiber filaments and the chitosan quaternary ammonium salt solution on the surface of the chitosan fibers can improve the suspension rate and stability, while having a larger specific surface area and a bonding effect after encountering water, so that the suspending agent can withstand rain erosion on weed leaves.
[0059] No citric acid fatty acid glyceride was added to the dispersant of Example 8. Compared with Example 1, the suspension rate of the suspending agent of Example 8 was lower than that of Example 1, and the stability score was lower than that of Example 1, and the difference was smaller than that of Example 1. This indicates that the addition of citric acid fatty acid glyceride can evenly disperse the starch-coated fat-soluble resin and nano-dispersed fibers in the suspending agent, while ensuring the suspension rate and stability. Citric acid fatty acid glyceride has a hydrophobic effect, which can make the suspending agent resistant to rain erosion on the surface of weed leaves.
[0060] Combining Example 1 and Comparative Examples 1-2 and Table 1, it can be seen that in Comparative Example 1, the starch-coated coumarone resin is replaced with an equal mass of coumarone resin in the raw material, and the starch-coated coumarone resin is replaced with an equal mass of starch in the raw material of Comparative Example 2. Compared with Example 1, the suspension rates of the suspension agents in Comparative Examples 1 and 2 are lower than those in Example 1, and the stability scores are lower than those in Example 1, and the difference is smaller than that in Example 1; this indicates that after the coumarone resin is gradually dissolved in the oil solvent, the viscosity of the suspension agent is increased, and the suspension rate and stability of the suspension agent are improved, while the starch is convenient for loading atrazine, nicosulfuron and mesotrione, further ensuring that the suspension agent has a higher suspension rate and higher stability, while the coumarone resin has a hydrophobic effect, making the suspension agent resistant to rain erosion on the surface of weed leaves, and the starch particles are convenient for adsorbing the oil solvent, further protecting the attachment stability of the suspension agent on the surface of weed leaves.
[0061] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A nicotine nitrate sulfonate atrazine oil suspension, characterized in that: The invention comprises the following raw materials in parts by weight: 40-50 parts of atrazine, 5-12 parts of nicosulfuron, 10-16 parts of mesotrione, 15-22 parts of emulsifier, 1-3 parts of starch-coated fat-soluble resin, 1-3 parts of nano-dispersed fiber, 1-2 parts of dispersant, 1-3 parts of thickener, 0.5-1 parts of defoamer and 50-60 parts of oil solvent.
2. A nicotine sulfonate atrazine oil suspension according to claim 1, characterized in that: The starch-coated fat-soluble resin is prepared from a starch composite liquid and coumarone resin in a mass ratio of 1:1-3.
3. A nicotine sulfonate atrazine oil suspension according to claim 2, characterized in that: The starch composite liquid is prepared from a starch solution, a phospholipid, glutaraldehyde and a sodium alginate solution in a mass ratio of 1:0.2-0.3:0.1-0.2:0.4-0.
8.
4. A nicotine sulfonate atrazine oil suspension according to claim 1, characterized in that: The nano dispersed fibers are made of cellulose nano fibers, chitosan fibers and hydrogenated rosin resin in a mass ratio of 1:0.1-0.5:0.2-0.
6.
5. A nicotine sulfonate atrazine oil suspension according to claim 4, characterized in that: The cellulose nanofibers are made of cellulose nanofiber filaments and sodium carboxymethyl cellulose solution in a mass ratio of 1:0.1-0.
3.
6. A nicotine sulfonate atrazine oil suspension according to claim 4, characterized in that: The chitosan fiber is made of chitosan fiber filaments and chitosan quaternary ammonium salt solution in a mass ratio of 1:0.2-0.
4.
7. The nicotine sulfonate atrazine oil suspension according to claim 1, characterized in that: The dispersant is composed of sodium lignin sulfonate and citric acid fatty acid glyceride in a mass ratio of 1:0.1-0.
5.
8. The nicotine sulfonate atrazine oil suspension according to claim 1, characterized in that: The emulsifier is castor oil polyoxyethylene ether.
9. The atrazine nicotinate oil suspension according to claim 1, characterized in that: The oil solvent consists of soybean oil, palm oil and orange oil in a mass ratio of 1:0.2-0.4:0.1-0.
3.
10. A method for preparing a nicotine sulfonate atrazine oil suspension according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, mixing and emulsifying the oil solvent and the emulsifier uniformly to obtain an emulsified solvent; S2, adding atrazine, nicosulfuron and mesotrione to the emulsified solvent, mixing and stirring evenly, and then sand-milling to obtain a mixture; S3. Add starch-coated fat-soluble resin, nano-dispersed fiber, dispersant, thickener and defoamer into the mixture, mix and stir evenly, and defoam to obtain the finished product.